Los juegos didácticos como estrategia en el aprendizaje de la matemática en los estudiantes del quinto grado de primaria de la institución educativa Fe y Alegría 46 Wilhelm Rossman Iquitos 2022 - Ruiz Gutierrez, Victor Hugo (2025)
Results are presented in relation to the research after applying a strategy of didactic games to improve the learning of Mathematics. The question was formulated: What is the effect of educational games as a strategy in improving the mathematics learning of fifth grade primary school students at the Fe y Alegría 46 educational institution –IQUITOS 2022? The proposed hypothesis, the application of didactic games, has a significant effect on the learning of mathematics of fifth grade primary school students at the Fe y Alegría 46 educational institution -IQUITOS 2022. The objective is to determine the effect of didactic games as strategy, in improving the mathematics learning of fifth grade primary school students at the Fe y Alegría 46 educational institution IQUITOS 2022. Type of applied research, pre-experimental design, single group. 30 students made up the population and the sample. The survey method and a proficiency test were utilized, both validated by experts. Pretest findings indicate that 46.7% of students attained the introductory level, 33.3% reached the intermediate level, and 20.0% reached the advanced level. In the post-test, 13.3% of students began at the introductory level, 6.7% at the intermediate level, and 80.0% ultimately achieved proficiency in this skill. Conclusively, using didactic games as a tactic significantly impacts the mathematics learning of fifth grade students at the Fe y Alegría 46 Iquitos educational institution in the year 2022.